THE KAREN PEOPLES OF MYANMAR: AN EXAMINATION OF ISSUES SURROUNDING KAREN COMMUNITIES IN MYANMAR AND THE APPLICATION AND IMPLEMENTATION OF HUMAN RIGHTS PRINCIPLES AND LAWS - Mendiolaza, Gustavo A (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
This paper explores the current and past practices of the government of Myanmar in its attempts to disenfranchise and disempower the sizeable minority of Karen peoples. The Karen, constituting a large community that stretches predominately over the two countries of Thailand and Myanmar is often overlooked because of the lack of readily available information regarding Myanmar in general and the Karen in particular. This paper views the issues that surround the Karen and the human rights violations they have suffered in the past 70 years at the hands of the dominant Burman government. Further, in attempts to tie this to the current Rohingya crisis in Myanmar’s southwest, this paper also intends to use predictive forecasting assessing the future endgame of Naypyidaw, the government of Myanmar.